The Growth of Plankton Model with Toxin———From the Perspective of Heterosigma Akashiwo - YANG Hong; LI Chengyu (Journal of Harbin University of Science and Technology)
In order to study the growth of phytoplankton in a toxic plankton model，we first take take the harmful algal bloom species，Heterosigma akashiwo，as an example and establish a multiple regression model between its growth rate and three influencing factors: temperature ，salinity ，and light intensity based on relevant literature data. The parameters of the model are determined. Secondly，using the theory of qualitative analysis of ordinary differential equations，we prove the positivity and boundedness of the solution of the model and analyze the stability of the model by considering the growth rate as a parameter. Finally，incorporating the obtained stability analysis conclusions，we quantitatively and specifically describe its growth situation with a numerical simulation. In conclusion，taking into account the influence of environmental factors on the growth rate and toxin release rate，and how they in turn affect the population dynamics of planktonic organisms in the biological system. This study has significant guiding implications for predicting the dynamic changes of planktonic organisms and forecasting harmful algal blooms by considering the impact of environmental factors on growth rate and toxin release rate.